Loss of cardiac synchronization due to automatic sense testing. Issue 9 (16th August 2022) - Römers, Hans; Liebregts, Max; Koyak, Zeliha; Balt, Jippe C.
Abstract: In the latest generation Biotronik cardiac resynchronization devices, cardiac resynchronization therapy (CRT) may be inadvertently interrupted due to automatic sense testing. This issue can easily be recognized during device interrogation by the "CRT interrupt warning."To avoid CRT interruption, both understanding of the algorithm and correct device programming are critical. The automatic sense testing algorithm has no built‐in protection to avoid CRT interrupted pacing. When implanting this generation of devices programming needs to be adequate to avoid the occurrence of this phenomenon.